Extracurricular Traditional Dance Art in Inculcating the Values of Tolerance and Love for the Homeland - Ramadani, Nopita (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
Character building has become one of the most prominent issues extensively discussed by many individuals. The influx of numerous foreign cultures across Indonesia's borders threatens the young generation's devotion to their motherland, particularly when they lack adequate education on tolerance and love for their country. They would end up comparing Indonesia's culture with popular foreign cultures, such as Korean culture like K-pop or the modern dance moves frequently seen on TikTok. Consequently, researchers have initiated investigations to explore ways of enhancing character-building among the younger generation through the incorporation of traditional dance, aiming to instill values of tolerance and love for their motherland. This study utilizes a qualitative evaluation method and employs a descriptive evaluation design. The sample for this research consists of 4th-grade students from SDN 2 Sambirejo, Wonogiri Regency. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, drawing conclusions, and verification. This research reveals a significant correlation between the implementation of character-building through traditional dances. By incorporating traditional dances as an extracurricular activity in schools, teachers can effectively instill values of tolerance and love for the motherland. Particularly, its effectiveness is enhanced when excellent facilities and competent teachers support the extracurricular activity. This is primarily because traditional dances in Indonesia reflect the diversity of Indonesian culture. Therefore, traditional dances are an additional effective means to foster a tolerant personality and cultivate a love for the motherland.